Gender bias in bargaining: Lessons from haggling over the price of seed in rural Uganda - Van Campenhout, Bjorn; Nabwire, Leocardia (International Food Policy Research Institute, 2024)
In developing countries, haggling over prices of goods and services is common practice. A range of personal, economic, social and cultural factors influence strategies used during the bargaining process—and ultimately its outcome. For example, bargaining between a government official who pulls up in an expensive SUV and a poor woman selling tomatoes in a roadside stall is likely to be very different from that of two traders of equal standing cutting a deal involving a few tons of maize.